The influence of a badminton competition with two matches in a day on muscle damage and physical performance in elite junior badminton players - Moreno-Perez, V.; Gallo-Salazar, C.; Del Coso, J.; Ruiz-Pérez, I.; Lopez-Valenciano, A.; Barbado, D.; Cabello-Manrique, D.; Fernandez-Fernandez, J. (Biology of Sport, 2020)
To investigate the effects of a badminton competition with 2 matches in a day on hip strength and range of motion (ROM) and exercise-induced muscle damage in elite junior badminton players. Twenty players (age: 17±0.8 years; body mass: 62.9±6.5 kg, height: 173.8±8.9 cm) participated in this study. Passive hip internal (IR) and external rotation (ER), abduction (ABD) and adduction (ADD) hip ROM, isometric hip ADD and ABD muscle strength, countermovement vertical jump (CMJ) height and blood creatine kinase concentration (CK) were measured before and after a badminton competition during an international tournament. Blood samples were collected 24 h after the end of the last match. Compared to baseline values, hip IR and ER ROM were significantly decreased at post-competition in the dominant (IR=-9.0%; p=0.007 and ER=-15.2%; p=0.002) and non-dominant limbs (IR=-9.08%; p=0.004 and ER=-19.4%; p<0.001). In contrast, hip ADD (13.5%; p<0.001) and ABD (14.6%; p<0.001) strength increased significantly after the competition in the dominant limb and ABD strength increased significantly in the non-dominant limb (9.2%; p=0.001). From baseline values, CK increased after the competition (430.1%) and values remained elevated over baseline values 24 h later (160.4%). Although hip muscle strength increased, a badminton competition with two consecutive matches reduced hip ROM and increased blood CK concentration. This study suggests the necessity of investigating recovery strategies after a badminton competition to return hip ROM to basal values before the next day of the competition.